Influence of Oxygen Carrier on the Autothermicity of a Chemical- Looping Reforming Process for Hydrogen Production - López van der Horst, Juliana (2025)
The chemical-looping reforming (CLR) of methane for hydrogen production employs a solid oxygen carrier (OC) and combines endothermic and exothermic stages, allowing for potential autothermal operation. This study conducted a thermodynamic analysis using Gibbs free energy minimization and energy balances to assess the behavior of WO3, MnWO4, and NiWO4 as OCs in the CLR process. The effects of CH4:OC ratios and reactor temperatures on equilibrium composition and the energy performance were examined. The results demonstrated that elevated reduction temperatures promote OC conversion and the formation of more reduced solid products. Molar ratios above stoichiometric prevent carbon formation, whereas stoichiometric ratios result in higher H2 yield, achieving 98% at 1000 ◦C. However, these conditions do not support autothermal operation, which requires CH4:OC molar ratios above stoichiometric. Additionally, lower oxidation temperatures are preferred regardless of the OC, due to the lower heat needed to preheat the air, which has a greater effect on the net heat. For the reduction temperature, its effect depends on the type of OC analyzed. The maximum H2 yield obtained under autothermal operation was 88% for the three OCs, at 875 ◦C for MnWO4 and 775 ◦C for both WO3 and NiWO4.